Estimation of Mycobacterium avium subsp. paratuberculosis load in raw bulk tank milk in Emilia‐Romagna Region (Italy) by qPCR. Issue 4 (17th March 2016) - Ricchi, Matteo; Savi, Roberto; Bolzoni, Luca; Pongolini, Stefano; Grant, Irene R; De Cicco, Caterina; Cerutti, Giulia; Cammi, Giuliana; Garbarino, Chiara A.; Arrigoni, Norma
Abstract: Consumption of milk and dairy products is considered one of the main routes of human exposure to Mycobacterium avium subsp. paratuberculosis (MAP). Quantitative data on MAP load in raw cows' milk are essential starting point for exposure assessment. Our study provides this information on a regional scale, estimating the load of MAP in bulk tank milk (BTM) produced in Emilia‐Romagna region (Italy). The survey was carried out on 2934 BTM samples (88.6% of the farms herein present) using two different target sequences for qPCR (f57 and IS900). Data about the performances of both qPCRs are also reported, highlighting the superior sensitivity of IS900‐qPCR. Seven hundred and eighty‐nine samples tested MAP‐positive (apparent prevalence 26.9%) by IS900 qPCR. However, only 90 of these samples were quantifiable by qPCR. The quantifiable samples contained a median load of 32.4 MAP cells mL −1 (and maximum load of 1424 MAP cells mL −1 ). This study has shown that a small proportion (3.1%) of BTM samples from Emilia‐Romagna region contained MAP in excess of the limit of detection (1.5 × 10 1 MAP cells mL −1 ), indicating low potential exposure for consumers if the milk subsequently undergoes pasteurization or if it is destined to typical hard cheese production. Abstract : The bulk tank milk from Emilia‐Romagna region (2934 samples) has been screened for the presence of Mycobacterium avium subsp. paratuberculosis by two qPCRs. Positive samples were also quantified by qPCR, indicating low potential exposure for consumers if the milk subsequently undergoes pasteurization.